Respuesta :

Answer:

[tex]\displaystyle x=\left\{0, \frac{2\pi}{3}, \frac{4\pi}{3}\right\}[/tex]

Step-by-step explanation:

We want to solve the equation:

[tex]-2\cos^2(x)=-\cos(x)-1[/tex]

Over the interval [0, 2π).

First, notice that this is in quadratic form. So, to make things simpler, we can let u = cos(x). Substitute:

[tex]-2u^2=-u-1[/tex]

Rearrange:

[tex]2u^2-u-1=0[/tex]

Factor:

[tex](2u+1)(u-1)=0[/tex]

Zero Product Property:

[tex]2u+1=0\text{ or } u-1=0[/tex]

Solve for each case:

[tex]\displaystyle u=-\frac{1}{2}\text{ or } u=1[/tex]

Back-substitute:

[tex]\displaystyle \cos(x)=-\frac{1}{2}\text{ or } \cos(x)=1[/tex]

Using the unit circle:

[tex]\displaystyle x=\left\{0, \frac{2\pi}{3}, \frac{4\pi}{3}\right\}[/tex]